حساب الساحة المغناطيسية في الثغرة الهوائية لآلة متواقتة ذات أقطاب غير بارزة وبنظام تهييج طولاني- عرضاني - حسن, عزت (Latakia University Journal -Engineering Sciences Series, 2019)
تمت دراسة طريقة التهييج الطولاني- العرضاني في الآلات المتواقتة ذات الأقطاب غير البارزة, نظراً لأهميتها في نظام استهلاك الاستطاعة الردية , والتخلص من حالات التهييج والاهتزاز الذاتيين, وأيضاً في تحسين مؤشرات الطاقة لهذه الآلات. كذلك تمت دراسة الساحة المغناطيسية في الثغرة الهوائية لتلك الآلة عند حالة التحميل واللاحمل تحليلياً وبيانياً باستخدام نظام الحاسب الآلي. تشير الدراسة إلى إمكانية استخدام هذه الطريقة في الآلات ذات الأقطاب البارزة أيضاً وعند حمولات متغيرة, وفي حالات مختلفة لإشباع الدارة المغناطيسية. This paper studies the Direct and quadrature (d-q)-excitation method in the non-salient poles synchronous machine (SM).This was done due to its importance in terms of reactive power consumption, excitation and auto vibrational case to improve and avoid the power parameters (performance parameters i.e.η and Cosφ). Studying of the magnetic field was also done in the air-gap for (SM) under load and non-load conditions, graphically and analytically, using computer. Our study suggestsusing such method in the salient poles, variable loads and at different saturation cases of the magnetic circuit.